Glibenclamide for the Treatment of Acute CNS Injury - Kurland, David B. (MDPI, 2013)
First introduced into clinical practice in 1969, glibenclamide (US adopted name, glyburide) is known best for its use in the treatment of diabetes mellitus type 2, where it is used to promote the release of insulin by blocking pancreatic K(ATP) [sulfonylurea receptor 1 (Sur1)-Kir6.2] channels. During the last decade, glibenclamide has received renewed attention due to its pleiotropic protective effects in acute CNS injury. Acting via inhibition of the recently characterized Sur1-Trpm4 channel (formerly, the Sur1-regulated NC(Ca-ATP) channel) and, in some cases, via brain K(ATP) channels, glibenclamide has been shown to be beneficial in several clinically relevant rodent models of ischemic and hemorrhagic stroke, traumatic brain injury, spinal cord injury, neonatal encephalopathy of prematurity, and metastatic brain tumor. Glibenclamide acts on microvessels to reduce edema formation and secondary hemorrhage, it inhibits necrotic cell death, it exerts potent anti-inflammatory effects and it promotes neurogenesis—all via inhibition of Sur1. Two clinical trials, one in TBI and one in stroke, currently are underway. These recent findings, which implicate Sur1 in a number of acute pathological conditions involving the CNS, present new opportunities to use glibenclamide, a well-known, safe pharmaceutical agent, for medical conditions that heretofore had few or no treatment options.